“We cannot live like Canadian”: Yazidi refugees’ perspectives on mental health, coping strategies and barriers to care - Bobyn, Jacqueline; Abraham, Bethel; Kain, Nicole; Williams, Kimberly; Coakley, Annalee; Watterson, Rita (Frontiers in Psychiatry, 2025)
BackgroundThe Yazidi people are a Kurdish religious minority group who have been persecuted by the Islamic State of Iraq and Syria (ISIS). The complexity of the trauma the Yazidi people endured, and a limited understanding of their illness belief models have created challenges to providing culturally sensitive psychiatric care. The purpose of this study was to use focus group methodology to understand Yazidi refugees’ experiences, to provide culturally informed mental health care.MethodsTwo in-person focus groups were held in Calgary, Alberta with Yazidi refugee women from Iraq and Syria (N = 6, N = 7) to assess perspectives on mental health, preferred coping strategies and perceived barriers to care. Participants were selected using purposive sampling. Focus group design and facilitation were done in partnership with Yazidi cultural brokers and interpreters. Focus groups were conducted in English and interpreted in Kurmanji. The focus groups were recorded, coded, and subjected to qualitative content thematic analyses. The analysis was guided by an interpretivist epistemology and informed by pragmatism, to situate participants’ perspectives within their social context while generating culturally informed insights for psychiatric care in Canada.ResultsExperiences with psychiatric symptoms (e.g. grief and loss, somatization, depression, trauma) were identified. Family reunification and community support were emphasized as preferred coping methods. Perceived unrealistic expectations of refugees post-migration, social isolation and language difficulties were acknowledged as barriers to care.ConclusionProviding appropriate psychiatric care to Yazidi refugee women requires a culturally informed approach. Findings in this study support the need for culturally sensitive mental health interventions in refugee populations post migration.